Rumah Bibit Sebagai Pondasi Penggunaan Ekonomi dan Wisata Masyarakat di Desa Sukamaju - Yoshiana, Annisa Asadifadillah; Yamani, Lucky; Trijayanti, Armiati; Insani, Novyanthy Ainun; Dewi, Lusiana; Novitasari, Nastiti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The direction of economic development policy emphasizes diverse and unique tourist attractions that can be widely developed. The development of tourist villages that prioritize empowerment and active community participation is one manifestation of this policy direction. There are, however, conditions in attracting participation. The community in the economic development and community tourism program does not know how to attract community participation in the economic development and community tourism program, in sustainable strategic steps in order to find solutions to these problems. Aims to know, understand and explain the urgency of developing sustainable tourism villages; and prepare a strategy analysis for developing sustainable tourism villages. a research method created in a technical way that describes the completion of work in a systematic way from start to finish which includes the stages and sequence of the main work and parts of how it works for each main work which can be accounted for systematically.